Mitophagy in Diabetic Kidney Disease - Zhang, Xiaofeng; Feng, Jing; Li, Xia; Wu, Dan; Wang, Qian; Li, Shuyu; Shi, Changhua (Frontiers in Cell and Developmental Biology, 2021)
Diabetic kidney disease (DKD) is the most common cause of end-stage kidney disease worldwide and is the main microvascular complication of diabetes. The increasing prevalence of diabetes has made the need for effective treatment of DKD critical and identifying new therapeutic targets to improve clinical management. Mitophagy is a highly conserved process that selectively removes damaged or unnecessary mitochondria via autophagic machinery. Given the important role of mitophagy in the increased risk of DKD, especially that with the recent rises in COVID-19-associated diabetic complications, this review should provide compelling evidence for maintaining homeostasis in the glomeruli and tubules, underlying mechanisms, and offer new insights into potential therapeutic approaches fortarget for the treatment of DKD.